2016
DOI: 10.1002/jnr.23859
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in depression during pregnancy and the postpartum period

Abstract: Women have a lifetime risk of major depression double that of men but only during their reproductive years. This sex difference has been attributed partially to activational effects of female sex steroids and also to the burdens of pregnancy, childbirth, and parenting. Men, in contrast, have a reproductive period difficult to delineate, and research on the mental health of men has rarely considered the effects of fatherhood. However, the couple goes through a number of potentially stressing events during the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 173 publications
(212 reference statements)
2
47
0
10
Order By: Relevance
“…Depression is relatively common across the population but is known to be more prevalent in females relative to males [18,[67][68][69][70]. Risk for depression in females doubles during pregnancy [71], which is thought to be due to a mixture of hormonal changes and a range of psychosocial factors [72][73][74][75] that may continue to impact on mental health throughout the lifespan [74].…”
Section: Discussionmentioning
confidence: 99%
“…Depression is relatively common across the population but is known to be more prevalent in females relative to males [18,[67][68][69][70]. Risk for depression in females doubles during pregnancy [71], which is thought to be due to a mixture of hormonal changes and a range of psychosocial factors [72][73][74][75] that may continue to impact on mental health throughout the lifespan [74].…”
Section: Discussionmentioning
confidence: 99%
“…How dietary diversity might interfere in the referred effects of anxiety and depression on the offspring has not been explored. It has been reported that nutritional status during pregnancy may also play an important role in the physical and mental development of offspring . Early nutritional exposures were independently related with increased risk of behavioral and emotional problems .…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the postpartum period involves changes not only in ovarian steroid levels but also in γ-Aminobutyric acid 19 -active progesterone metabolites, the hypothalamus-pituitary-adrenal axis, and the oxytocinergic system 4, 20 . In addition, the postpartum period is characterized by both attenuated serotonergic activity 2124 and decreased cortical GABA concentrations 25 .…”
Section: Discussionmentioning
confidence: 99%